Peran Sistem Pengarsipan dalam Meningkatkan Mutu Pendidikan di Sekolah Dasar Negeri 49 Kota Bengkulu - Deli Meylindo; Reindo Febrianto (UIN Fatmawati Sukarno Bengkulu, 2024)
Abstract: An organized and systematic Filing System is the key to managing information and documents, but it has not played an optimal role in improving the quality of education, this can be seen as still difficult to find correspondence documents during accreditation. The purpose of the research is to describe the role of the archiving system in improving the quality of education in 49 public elementary schools in Bengkulu City. Using a qualitative method of descriptive approach, involving observation, in-depth interviews with teaching and administrative staff, and analysis of school documents. The results of the study show that the role of the archiving system in general is good, seen not only to increase administrative efficiency, but also to support decision-making in planning and evaluating educational programs. In addition, neat archiving helps in facilitating communication between stakeholders, including teachers, parents, and the school. However, in an effort to improve the quality of education that has not been optimally carried out, it is still difficult to find important documents in schools. Thus, it can be concluded that the role of the archiving system can improve the quality of education, thus recommending further development in archiving practices to achieve more optimal results.Keywords: Role, Filing System, Quality of Education, Elementary School. Abstrak: Sistem Pengarsipan yang terorganisir dan sistematis menjadi kunci dalam pengelolaan informasi dan dokumen, namun belum berperan secara optimal dalam meningkatkan mutu pendidikan, hal ini terlihat masih kesulitan menemukan dokumen persuratan saat akreditasi berlangsung. Tujuan Penelitian untuk mendeskripsikan peran system pengarsipan dalam meningkatkan mutu pendidikan di sekolah dasar negeri 49 Kota Bengkulu. Menggunakan metode kualitatif pendekatan deskriptif, melibatkan observasi, wawancara mendalam dengan staf pengajar dan administrasi, serta analisis dokumen sekolah. Hasil penelitian menunjukkan bahwa peran system pengarsipan secara umum sudah baik, terlihat tidak hanya meningkatkan efisiensi administrasi, tetapi juga mendukung pengambilan keputusan dalam perencanaan dan evaluasi program pendidikan. Selain itu, pengarsipan yang rapi membantu dalam memfasilitasi komunikasi antar stakeholder, termasuk guru, orang tua, dan pihak sekolah. Namun dalam upaya peningkatan mutu pendidikan belum optimal dilakukan terlihat masih sulit menemukan dokumen surat-surat penting di sekolah. Dengan demikian, dapat disimpulkan bahwa peran sistem pengarsipan dapat meningkatkan mutu pendidikan, sehingga merekomendasikan pengembangan lebih lanjut dalam praktik pengarsipan untuk mencapai hasil yang lebih optimal.Kata kunci: Peran, Sistem Pengarsipan, Mutu Pendidikan, Sekolah Dasar.